From Autarky to Integration : Imitation, Foreign Borrowing, and Growth. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
The effects on growth of the integration of an autarkic country into the world economy are analyzed, focusing on the differing roles of imitation and innovation in human capital accumulation. The country initially concentrates on imitation of foreign knowledge; subsequently, as it approaches the knowledge frontier, innovation plays a greater role. Late developers catch up with the rest of the world more rapidly than early developers, reflecting the relatively large imitation opportunity available to them. Restrictions on foreign borrowing reduce the speed of adjustment to the steady state and lower growth and welfare for the country that imposes them.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet